Value of Children in Javanese Mothers to Children with Autism Spectrum Disorder: A Descriptive Study - Nannessi, Linda Benita; Handayani, Penny (Psychological Research on Urban Society, 2022)
The value of children lies in the way parents view their children. The perception of parents is influenced by the culture they adopt and live by, socioeconomic status, the gender of the child, and the number of children in the family. The purpose of this research was to look at the description of the value to Javanese mothers of children with autism spectrum disorder (ASD). The method used is quantitative (nonparametric statistical calculations) with descriptive techniques. There were 30 participants in the study using convenience sampling data collection techniques. The required characteristics of the participants were mothers of children with ASD who applied Javanese parenting culture. The results of normality with a value of asymp= .00 (p < .05) so that it is stated that the data is not normally distributed. The resultant value of children to mothers of children with ASD that stands out is the family dimension, so according to this study children with ASD can strengthen relationships within families, such as parents who provide social support to each other and siblings who become more empathic towards their siblings who have ASD.